A Study on Psychological Autopsy of Suicidal Cases of North Bengal Region (Indian Journal of Forensic Medicine & Toxicology, 2024)
There are times when physical evidence found at post-mortem examination does not uncover the cause and mode of death. This is known as equivocal death. The psychological autopsy is an attempt to reconstruct the decedent’s life to get a better understanding of his cause of death. It is used to determine the victim’s psychological intent, using interviews and examination of documents to reconstruct the behaviour, personality, lifestyle, habits and history of the victim prior to death. Psychological autopsy helps as an investigative instrument which requires an application of abilities, experience, and training to assess a variety of factors including the behaviour, thoughts, feelings, and relationships of an individual who is deceased. There may be situations that the family members of the deceased does not want to reveal thefacts about his death. Hence the counselling and interviews of family members, friends, and relatives has to be done with empathy. So the interviewer has to be flexible. The interviewer should establish mutual respect and confidence, with the informant, and ensure confidentiality and anonymity, and also obtain an informed consent before the interview. Hence one should be qualified and skilled to conduct the interview. False information also can be given due to lack of memory or it may be intentional. Suicide note, Personal documents, Medical records, school records, military records, employment records, should be carefully analysed. With the above mentioned information, a psychological autopsy report is produced, the final conclusion depends on the accuracy of the data collected from the interviews, examination of relevant documents and other materials. Therefore the interviewee’s probabilities and limitation to science should be noted. Thus the final judgement as to the mode of death is based upon a review of all the known facts and circumstances; including the coroner’s report, forensic medical report, police reports, crime scene analyst reports, and the psychological reconstruction ,so that people may learn from the tragedy and, hopefully, be cautious and reduce the chances of similar occurrence in future. Psychological autopsy is most often used in cases of suspected suicide or homicide in an attempt to reconstruct the personal life and character of the deceased, to uncover hidden facts that may help to give family members peace of mind and also plays a role in revealing the manner of death.
Keywords: Psychological autopsy; Suicide; Behaviour; Autopsy